2020
DOI: 10.1371/journal.pone.0243527
|View full text |Cite
|
Sign up to set email alerts
|

Worry and insomnia as risk factors for depression during initial stages of COVID-19 pandemic in India

Abstract: The biggest nationwide COVID-19 pandemic lockdown worldwide was enforced in India for an initial period of 21-days. Emerging evidence suggests that pandemic situations and associated lockdowns have an adverse impact on sleep and mental health. However, prediction of sleep health from sociodemographic characteristics and the public’s worry during the initial stages of the COVID-19 pandemic has not been extensively explored so far. It’s also unclear whether sleep outcomes mediate the association between worry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 78 publications
6
29
0
Order By: Relevance
“…A total of 250 studies [285 subgroups, i.e., multiple populations, multiple tools, or multiple data points] comprising 493,475 participants from 49 countries were included in the analyses [ [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [10...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 250 studies [285 subgroups, i.e., multiple populations, multiple tools, or multiple data points] comprising 493,475 participants from 49 countries were included in the analyses [ [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [10...…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that females were a high-risk population for insomnia [ 59 ]. A meta-analysis revealed the prevalence of insomnia in females was higher than that in males [ 60 ]; also, females were the predicted risk factor of insomnia during the COVID-19 pandemic [ 61 , 62 ]. Our results supported previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of any other published longitudinal study that has tracked COVID-related worry and rumination over the course of the pandemic or that has investigated whether weeks with higher COVID-related worry and rumination were associated with more negative mental health outcomes. A small number of studies have investigated the effects of worry and rumination early in the pandemic (e.g., Bajaj et al, 2020;Baker & van Wingerden, 2021). For example, Bajaj and colleagues (2020) showed that COVID-related worry was associated with more severe depressive symptoms during the initial 21-days of the first lockdown in India (starting 25 th March 2020).…”
Section: Discussionmentioning
confidence: 99%